1910
DOI: 10.5962/bhl.title.18835
|View full text |Cite
|
Sign up to set email alerts
|

Food for plants / Harris and Myers ; edited and published by William S. Myers.

Abstract: Hops 600 lbs. seed. 84 lbs. * be fertilized, without proper preparation of the soil the result must be more or less a failure. In top-dressing it is very important that the Nitrate of Soda be thoroughly ground, so an even distribution can be made; the fertilizer must go to the plant, not the plant to the fertilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1955
1955
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Since the seminal work of Modigliani and Miller (1958), it has been well accepted that capital structure is one of the important determinants of firm value. 1 Many studies have identified determinants of capital structure. Among these determinants is the agency cost resulting from the conflicts of interest in the classic agency setting of managers versus shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work of Modigliani and Miller (1958), it has been well accepted that capital structure is one of the important determinants of firm value. 1 Many studies have identified determinants of capital structure. Among these determinants is the agency cost resulting from the conflicts of interest in the classic agency setting of managers versus shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…11/, 22 (1960). (8 '(I')4 "K)')=(5/16 )~.o~o (8)', &i (5 16) where (8,)= - (8) independent of i. Finally, since we did not take account of the bandwidth of rotational excitations in Eq.…”
mentioning
confidence: 99%
“…The current per unit length flowing around the soliton is ∼ eρ/hδ and the characteristic loop area of the circulating currents is ∼ dδ where d is the layer separation. For typical parameters, these currents produce a magnetic induction directed along the soliton axis with magnitude ∼ 0.1µ B /ℓ 2 δ, which could in principle be detected by a SQUID or with cantilever-based [15] magnetometers.…”
mentioning
confidence: 99%